Quantitative Analysis of Mineral Elements in Commercial Pineapple Juices by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) - YOUSSAO ABDOU KARIM, ALASSANE; GBAGUIDI, ACAKPO NONVIGNON MAGLOIRE; Baltrons, Oriol; SEBY, Fabienne; MONPERUS, Mathilde; SOCLO, HOUÉNOUKPO HENRI; DONARD, F. Olivier (My University, 2018)
The consumption of fruit juice in the diet has increased in recent years because it contains mineral food supplements and other essential vitamins. In this study, sugar levels and mineral nutrient concentrations were evaluated in 92 commercial pineapple juice samples from Benin and France using inductively coupled plasma mass spectrometry (ICP-MS). The analysis of the data obtained reveals three ranges of concentrations relative to major elements or macro-elements (Ca, Mg), to minor elements or micro-elements (Mn, Fe, Ni, Cu, Zn), and to trace elements (Mo, V, Co, Cr). The concentrations of macro-elements and micro-elements (expressed in μg/L) vary from 11333 to 278000 for Mg, 95200 to 788000 for Ca, 536 to 25344 for Mn, 142 to 85612 for Fe, 5 to 253 for Ni, 5 to 1256 for Cu, and from 43 to 25862 for Zn. The trace elements were found in the concentration ranges (expressed in μg/L) of: 0.23 - 12.50 for Vanadium, 0.58 - 17.10 for Cobalt, 1.17 - 58.70 for Molybdenum and finally 4 - 70.5 for Chromium. The sugar levels in the various commercial juices collected in Benin and France vary from 11.0 to 18.5 Brix with an average value of 14.0 Brix. Apart from the heterogeneous nature of the juices produced in Benin production units, mineral and sugar levels were generally in accordance with international standards such as CODEX STAN 182-1993. The transformation of pineapple into fruit juice is a credible alternative for the improvement of pineapple exports, if the marketing strategy is better adapted and the local authorities support the manufacturers of the production chain to improve the quality of juices and highlight their excellent nutritional quality.
Keywords: Minerals; Juice; Pineapple; Benin; France; Codex Stan; ICP-MS